Modelling the stored energy of plastic deformation for individual crystal orientations. Issue 1 (April 2015) - Shore, D; Van Bael, A; Sidor, J; Roose, D; Van Houtte, P; Kestens, L
Abstract: Recovery and recrystallisation processes in polycrystalline metals are driven by the release of energy stored in defect structures chiefly resulting from dislocation creation, motion and interaction during plastic deformation. Some statistical models of texture change during recrystallisation employ the Taylor factor to quantify the distribution of this stored energy amongst orientations. While the Taylor factor is an instantaneous measure of the plastic power dissipation per orientation for a given strain mode, it is technically only valid as an estimate of stored energy if strain path and texture can be assumed constant. This motivates the search for alternatives to the Taylor factor which do not neglect the effects of changing strain path and evolving texture. In this paper a first step is made toward this goal by comparing the Taylor factor with a possible alternative, the accumulated slip per orientation, for a plane strain compression deformation of a bcc material. It is discovered that even for this idealised deformation there are specific orientations for which there is a consistent difference between the two parameters at various magnitudes of strain. It is concluded that these results lend support to the case for replacing the Taylor factor with a history based parameter in recrystallisation texture models.